Volume Visual Attention Maps (VVAM) in Ray-Casting Rendering (2012)
This paper presents an extension visual attention maps for volume data visualization, where eye fixation points become rays in the 3D space, and the visual attention map becomes a volume -- This Volume Visual Attention Map (VVAM) is used to interactively enhance a ray-casting based direct volume rendering DVR visualization -- The practical application of this idea into the biomedical image visualization field is explored for interactive visualization